The Effect of Human Relations (Human Relations) and Organization Based Self Esteem on the Work Ethos of Maluku Audit and Financial Audit Agency Representatives - Rehatta, Pieter N.R; Tutupoho, Saleh; Tuasuun, Zhasia I. (SEAN Institute, 2024)
This research was conducted based on the phenomenon at BPKP to provide suggestions regarding the problems faced by the personnel of the Maluku Province BPKP Representatives and to find out how much influence Human Relations and Organization Based Self Esteem had on the work ethics of the Maluku Province BPKP Representatives. The type of research used is quantitative research using primary data in the form of interviews, questionnaires and library research which is carried out regularly based on research objectives to BPKP employees of Maluku Province. The sample collection technique in this study used a saturated sample (non probability sampling), that is, by using all members of the population to be used as a sample. The results showed that (1) Human Relations had a significant positive effect on Work Ethics and (2) Organization Based Self Esteem had a positive effect. Significance of Work Ethics